2017
DOI: 10.1016/j.anucene.2016.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the response of Autonomous Reactivity Control (ARC) systems

Abstract: The Autonomous Reactivity Control (ARC) system was developed to ensure inherent safety of Generation-IV reactors while having a minimal impact on reactor performance and economic viability. In this study we present the transient response of fast reactor cores to postulated accident scenarios with and without ARC systems installed. Using a combination of analytical methods and numerical simulation, the principles of ARC system design that assure stability and avoids oscillatory behavior have been identified. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These types of control devices were successfully demonstrated at the Fast Flux Test Facility [12]. A similar approach using a lithium injection device was proposed for reactivity control in breed-burn fast reactors [14], and transient analyses showed that this type of device could enable fast reactors with large positive coolant temperature reactivity coefficients to operate safely [15]. Additionally, mechanisms such as grid-plate expansion and axial fuel expansion could help reduce the large coolant temperature reactivity coefficient in both metal-and oxide-fueled cores.…”
Section: Discussionmentioning
confidence: 99%
“…These types of control devices were successfully demonstrated at the Fast Flux Test Facility [12]. A similar approach using a lithium injection device was proposed for reactivity control in breed-burn fast reactors [14], and transient analyses showed that this type of device could enable fast reactors with large positive coolant temperature reactivity coefficients to operate safely [15]. Additionally, mechanisms such as grid-plate expansion and axial fuel expansion could help reduce the large coolant temperature reactivity coefficient in both metal-and oxide-fueled cores.…”
Section: Discussionmentioning
confidence: 99%
“…In response to needs identified by a Nuclear Energy University Partnership project, new mathematical operations were required to represent the reactivity feedback characteristics of an Autonomous Reactivity Control device. [11] The behavior of an ARC device can be represented by a variable lag compensator. A variable lag compensator is similar to a lag compensator except that the delay time parameter can vary during the Control System simulation.…”
Section: Control System Extensionmentioning
confidence: 99%